2000
DOI: 10.1111/j.1528-1157.2000.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐Life and Behavioral Outcome Measures in Randomized Controlled Trials of Antiepileptic Drugs: A Systematic Review of Methodology and Reporting Standards

Abstract: Summary: Purpose:To review the methodology and use of quality-of-life and behavioral measures used in randomized controlled trials (RCTs) of antiepileptic drugs in patients with epilepsy.Methods: Trial reports were found by searching a previously developed comprehensive database of epilepsy RCTs and searching through journals by hand. Inclusion and exclusion criteria were applied, and methodological and quality-of-life and behavioral measure data were extracted.Results: There were 52 different measures used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…24 Subjective Global Assessment was designed for use in the prediction of risk for complications after general surgery based on preoperative nutritional state, 25 whereas Mini Nutritional Assessment, the third valid tool, was developed as a screening and assessment tool to identify geriatric patients at risk for malnutrition. 32 Although both SGA and Mini Nutritional Assessment have been validated subsequently for use in other disease or injury states, neither has been validated for the assessment of individuals with stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Subjective Global Assessment was designed for use in the prediction of risk for complications after general surgery based on preoperative nutritional state, 25 whereas Mini Nutritional Assessment, the third valid tool, was developed as a screening and assessment tool to identify geriatric patients at risk for malnutrition. 32 Although both SGA and Mini Nutritional Assessment have been validated subsequently for use in other disease or injury states, neither has been validated for the assessment of individuals with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…30 The prestroke living arrangements for subjects in the included studies were not usually reported so it is difficult to know whether a larger or smaller percentage of subjects were malnourished at the time of entry into the study. On the basis of this review, we cannot claim to have established the true prevalence of malnutrition poststroke; however, because it is now generally accepted that reliable and valid measurement is essential for the generation of meaningful and replicable data and interpretable results, 31,32 the estimates obtained from the 4 studies using a valid nutritional assessment method may have been less biased and more likely to have yielded a truthful result. If so, then malnutrition is less prevalent than previously thought.…”
Section: Foley Et Al Estimates Of Malnutrition Poststroke E71mentioning
confidence: 99%
“…When the health condition is associated with cognitive difficulties, a cognitive dimension should be added, which is closely related to all the four abovementioned dimensions, and which can be itself subdivided: Overall cognitive functioning, language, memory, attention, etc. For patients with epilepsy, Baker et al [5] found 52 different QoL and behavioural outcome measures which have been used in randomized control trials of antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the quality of continuous outcome measure reporting have primarily focussed on publication bias [2, 3] and the suitability and reporting of the psychometric properties of the measures [4, 5]. The reporting of scoring and interpretation details for continuous outcome measures in randomized trials has not been investigated.…”
Section: Introductionmentioning
confidence: 99%